Strengthening the historical ties between Serbia and Cyprus in view of 21st century challenges and opportunities in Europe: The elevated geostrategic position in the Balkans and Eastern Mediterranean, the common legacy of neutrality and future engagement - Theophylactou, Demetrios (Napredak, 2021)
The foundations of the strong historical ties between Serbia and Cyprus lie on common struggles, dating back to the 19th and 20th centuries, particularly during the two great wars. Their long struggles against various aggressors, like the Ottoman Turks, Nazi Germany and British colonialism, have left long-lasting wounds on their societies, but also a legacy of bravery, resilience, perseverance and national pride. The deep friendship is also premised on common cultural and Orthodox roots, which helped the two peoples overcome major challenges and preserve their national identity and cultural values. This analysis explores the challenges ahead and assesses the new strategic partnership, including the trilateral cooperation between Serbia-Greece-Cyprus, particularly in light of EU enlargement in the Western Balkans and the volatile situation in the Eastern Mediterranean. The article also attempts to evaluate how the policy of neutrality, that both Yugoslavia and Cyprus have pursued as founding members of the Non-Aligned Movement, would serve today the national interests of Serbia and Cyprus and, by extension, stability and security in their respective regions and the European continent at large, given their elevated geostrategic position.